Makna Kehilangan Ayah bagi Mahasiswa Studi Kualitatif Perbedaan Fatherless Akibat Perceraian dan Kematian - Mega Sylvia Dewi; Dewi Sukmawati; Sri Mulyeni (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The absence of a father figure (fatherlessness) can have significant impacts on an individual's psychological and social well-being, particularly among university students who are navigating the critical phase of identity formation. This study aims to explore the meaning of father loss in students by comparing experiences of losing a father due to divorce and death. Using a qualitative phenomenological approach, six participants who had experienced fatherlessness were interviewed in depth. The results show that the loss of a father due to death is generally perceived as a permanent and irreplaceable loss, evoking deep sadness. In contrast, father loss due to divorce is often associated with emotional conflict, feelings of abandonment, and unresolved grief (ambiguous loss). The psychological impacts include emotional disturbances, social difficulties, and low self-confidence. Students employed various coping strategies such as seeking social support and engaging in academic or productive activities. In conclusion, the study highlights that the meaning of father loss varies depending on its cause, but both types have significant negative effects on students' psychological well-being. Therefore, strong emotional and social support is essential to help fatherless students adapt and build resilience in facing such loss.